Do financial markets react to Bank of England communication? - Rachel Reeves; Michael Sawicki (Bank of England, External Monetary Policy Committee Unit, 2005)
The effectiveness of a central bank's monetary policymaking is determined by the merit of its policy actions and their perceived credibility. Since the 1990s central banks have placed more emphasis on clear communications and transparency as additional levers to help achieve their goals. In this paper we examine how UK financial markets react to Bank of England communication. We might expect interest rate expectations, and potentially other asset prices, to react to official communication if such communication helps inform market participants. We find evidence that the publication of the Minutes of the Monetary Policy Committee meetings and the Inflation Report significantly affect near-term interest rate expectations, an effect particularly visible in intraday data. Speeches and parliamentary committee hearings appear to have less of an impact. Our results for the UK are arguably less strong than Kohn and Sack's (2003) findings for US Federal Reserve communication. Although differences in institutional frameworks between the UK and US mean communications are not directly comparable, our results might also reflect the different mandates of the FOMC and the MPC, with the Federal Reserve having greater freedom to interpret its objectives.
Keywords: E44; E52; E58; G14; 330; Finanzmarkt; Zentralbank; Kommunikation; Geldpolitik; Großbritannien